Revenue Generation Initiatives in Technical-Vocational Schools in Northern Samar: Basis for a Framework Design - Doncillo, Jennifer (Journal of Interdisciplinary Perspectives, 2025)
Revenue-generation initiatives are a potential strategy to aid school needs, yet their implementation needs further scrutiny. This study, therefore, assessed the revenue generation initiatives (RGI) and their benefits to the technical vocational schools in the first district of Northern Samar, Philippines, as a basis for the framework design. It employed a mixed-methods approach, specifically using an explanatory sequential design, which utilized a self-structured survey questionnaire and an interview guide. Respondents of the study were nine (9) school heads and RGI coordinators, respectively, and one hundred forty (140) technical vocational and livelihood (TVL) teachers. To analyze and interpret the data for the quantitative aspect, descriptive statistics such as frequency and percentages, average, mean, and standard deviation were utilized. For the qualitative aspect, thematic analysis was applied. Findings revealed that among the types of income-generating activities, school canteens or cafeterias are the most common, occurring in 9 schools (40.91%). Most implement 2 (44.44%) revenue-generating activities. Most (5 or 55.56%) earned an average annual income of Php40,000 to Php79,999.00. Most (5 or 56%) have 1-5 staff members. The majority, 8 (88.89%), have been operating for a short period (5 to 13 years). Their management practices are generally “Highly Practiced” (x=437; SD=0.41). The revenue generation initiatives (RGIs) have significantly contributed to employment creation, school improvement, allocation of resources for teaching and learning, innovation, technological development, market expansion, and skills development. However, the study revealed several challenges, including institutional issues, financial constraints, time and role management, management capacity gaps, and difficulties in stakeholder engagement. A revenue generation framework has been designed to enhance the implementation of revenue-generating initiatives in technical-vocational schools in Northern Samar, further emphasizing key components such as maximizing income potential and operational efficiency, improving time and cost management, expanding RGIs as platforms for employment, learning, and innovation, and addressing systemic and operational barriers.